A role for collagen XXIII in cancer cell adhesion, anchorage-independence and metastasis. - Spivey, K.A.; Chung, I.; Banyard, J.; Adini, I.; Feldman, H.A.; Zetter, B.R. (2012)
Collagen XXIII is a transmembrane collagen previously shown to be upregulated in metastatic prostate cancer that has been used as a tissue and fluid biomarker for non-small cell lung cancer and prostate cancer. To determine whether collagen XXIII facilitates cancer cell metastasis in vivo and to establish a function for collagen XXIII in cancer progression, collagen XXIII knockdown cells were examined for alterations in in vivo metastasis as well as in vitro cell adhesion. In experimental and spontaneous xenograft models of metastasis, H460 cells expressing collagen XXIII shRNA formed fewer lung metastases than control cells. Loss of collagen XXIII in H460 cells also impaired cell adhesion, anchorage-independent growth and cell seeding to the lung, but did not affect cell proliferation. Corroborating a role for collagen XXIII in cell adhesion, overexpression of collagen XXIII in H1299 cells, which do not express endogenous collagen XXIII, enhanced cell adhesion. Consequent reduction in OB-cadherin, alpha-catenin, gamma-catenin, beta-catenin, vimentin and galectin-3 protein expression was also observed in response to loss of collagen XXIII. This study suggests a potential role for collagen XXIII in mediating metastasis by facilitating cellâcell and cellâmatrix adhesion as well as anchorage-independent cell growth.